Examination of the effect of the gender factor on university students’ physical activity level (Bangladesh Journal of Medical Science, 2020)
Objective: Scientific research provide information concerning an insufficient level of physical activity of young people. This study was conducted to determine the levels of physical activity among university students.Materials and Methods: In 2014-2015 academic year, 510 students voluntarily participated in this study. To obtain data, the Personal Information Form and to determine the levels of physical activity. International Physical Activity Questionnaire (IPAQ) were used.Results and Discussion: It is found that the 32.8% of students were not physically active, 49.2% of them had low physical activity level, 18% of students had adequate physical activity level to protect their health. Although it was found that the male students’ physical activity scores, moderately intense activity scores, intense activity scores and walking activity scores significantly higher than girls’ activity scores (p